Clinical and endocrinological manifestations of childhood-onset craniopharyngioma before surgical removal: A report from one medical center in Taiwan - Ching-Chih Huang; Kuang-Lin Lin; Chieh-Tsai Wu; Shih-Ming Jung; Chao-Jan Wang; Yi-Ching Chen; Fu-Sung Lo (Pediatrics and Neonatology)
Background: Craniopharyngiomas are benign tumors of embryologic origin located in the sellar region. Patients have both neurological and endocrinological symptoms. Symptoms may be subtle in the early clinical course, which leads to delayed diagnosis. This study evaluated the clinical and endocrinological manifestations of childhood-onset craniopharyngioma. Methods: We retrospectively reviewed medical records of 45 children diagnosed as having craniopharyngioma between 1995 and 2019. We collected data on clinical symptoms and signs, height, weight, biochemical and hormone data, images, operation records, and pathology reports. A three-graded classification system was applied to define the degree of hypothalamic damage (HD). We analyzed clinical and endocrinological manifestations among patients with and without obesity, with short and normal stature, and with differing degrees of HD. Results: Clinical endocrinologic manifestations included adrenocortical insufficiency (42%), central hypothyroidism (37%), short stature (31%), obesity (20%), weight < third percentile (19%), and polyuria or polydipsia (11%). The distribution of height and body mass index (BMI) revealed that a relatively large proportion of patients had short stature and obesity compared to the general population. Patients with grade 2 HD were significantly taller (height median SDS −0.07 vs. −2.05, P = 0.032), and had higher BMI (BMI median standard deviation scores [SDS] 1.14 vs. −0.54, P = 0.039) and shorter time to diagnosis (0.27 vs. 8.29 months, P = 0.007) than were those in the grade 0–1 HD. Delayed diagnosis was associated with short stature (6/7 vs. 4/26, P = 0.001) and no initial neurological symptoms (4/7 vs. 2/28, P = 0.009). Conclusion: Growth patterns may change variously depend on the tumor location and the severity of hypothalamic damage. Therefore, monitoring possible neurological symptoms and evaluating the growth patterns of patients during regular outpatient clinical visits are paramount.